COMPARISON OF THE PERFORMANCE OF SHARIA STOCK MUTUAL FUNDS WITH THE TREYNOR, SHARPE, AND JENSEN METHODS DURING THE RECESSION IN INDONESIA - Tryas Chasbiandani; Eka Sudarmaji; Afifa Nudiya Sari (INQUISITIVE : International Journal of Economic, 2021)
During the economic recession, mutual funds can be used as an investment method to help fund circulation and revive the economy of country which has been affected by the Covid-19 pandemic. Investors can find out the mutual fund performance by measuring the risk adjusted return in order that investment can be maximized. The aim of this research is to compare the performance of sharia equity mutual funds and foreign securities based equity mutual funds during economic recession in January 2019 to October 2020 which divided into two periods, before the covid-19 pandemic from January 2019 to February 2020 and after the covid-19 pandemic from March to October 2020. The measurement of mutual fund portfolio performance uses the Treynor, Sharpe, and Jensen methods. They are based on purposive sampling which results the samples of 32 (thirty two) mutual funds from 25 (twenty five) investment managements. The results of the performance comparison show that Cipta Saham Unggulan Syariah which belongs to PT Ciptadana Asset Management provides the best return among its competitors where this mutual fund is able to exceed the benchmark before recession -0,0124 and after recession -0,0046 using the three methods.